Queen Mother : Black nationalism, reparations, and the untold story of Audley Moore - Farmer, Ashley D. (Pantheon, 2025)
"From an award-winning historian of Black radical politics comes the definitive biography of Audley Moore -- mother of modern Black nationalism and trailblazer in the fight for reparations. In the world of Black radical politics, the name Audley Moore commands unquestioned respect. Across the ten decades of her life, Queen Mother Moore distinguished herself as a leading forebear of Black Nationalism, the founder of the modern reparations movement, and, from her Philadelphia and Harlem homes, a mentor to some of America's most influential Black activists. And yet, she is far less remembered than many of her peers and protégés -- Marcus Garvey, Malcolm X, and Muhammad Ahmad, to name just a few -- and the ephemera of her life have been either lost or plundered. In Queen Mother, celebrated writer and historian Ashley D. Farmer restores Moore's faded portrait, delivering the first-ever account of her life and enduring legacy. Deeply researched and richly detailed, Queen Mother is more than just a biography of an American icon. It's a narrative history of twentieth-century Black radicalism, told through the lens of the woman whose grit and determination sustained the movement"--